State of Knowledge on Gender and Resilience: What Does the Evidence Show? - Bryan, Elizabeth (2022)
Presented by Elizabeth Bryan, Senior Scientist, Environment and Production Technology Division (EPTD), International Food Policy Research Institute (IFPRI), June 8, 2022. This presentation was for a lightning session on gender and resilience at a USAID Center for Resilience Cross-Agency Resilience Learning Event.